Development of high-speed rail in the People's Republic of China - Pan Haixiao; Gao Ya (Asian Development Bank Institute (ADBI), 2019)
High-speed rail (HSR) construction is continuing at a rapid pace in the People's Republic of China (PRC) to improve rail's competitiveness in the passenger market and facilitate inter-city accessibility. To take advantage of spillover effects, bring economic cohesion at the local level, and recover the local matching investment in infrastructure, all cities have planned new towns around HSR stations. Speeding up HSR construction has required the development of many standardized technologies and processes. Plans for HSR stations usually situate them in suburbs, far from city centers, to reduce the cost of property right of way relating to the removal of housing or industry as well as to lower the complexities in negotiations. However, city centers remain the main starting and destination terminals for most HSR passengers, especially businessmen who use HSR frequently. Besides, large railway stations in suburbs, providing a comfortable waiting space for passengers, have prolongate the travel time for HSR users. A reliable and high-quality public transit service, connecting an HSR station and the city center at the launch of HSR operations, is essential to curb the increase in car/taxi use. Studies have also suggested that, instead of building one big HSR station in the suburb of a metropolis, constructing multiple stations in the vicinity of city centers will greatly reduce the access/egress time, thereby enhancing the travel efficiency.
Keywords: L92; R11; R40; R58; 330; high-speed rail; multimodal intercity transport; People's Republic of China